PENERAPAN HARGA, KUALITAS LAYANAN DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN BINTANG MAS SELLULER - Triafrizal, Zyira Avian; Octavia, Ayu Nurafni (JURNAL PUNDI, 2025)
This research is motivated by the increasingly tight market competition, where consumer purchasing decisions are an important factor for business success. Bintang Mas Selluler faces the challenge of understanding the influence of price implementation, service quality, and promotion in influencing customer purchasing decisions. Competitive prices, quality services, and effective promotions are believed to be the main elements that influence consumer purchasing decisions. This study uses a quantitative approach with a sample of 96 respondents selected using purposive sampling techniques. Data were collected through questionnaires that had been tested for validity and reliability. Data analysis was carried out through the stages of classical assumption tests, including multicollinearity, heteroscedasticity, and normality tests. The main analysis used multiple linear regression, supported by the t-test to test the partial effect of independent variables and the coefficient of determination test to evaluate the extent to which the model can explain the dependent variable. The results of the study indicate that price implementation has a positive and significant effect on purchasing decisions, service quality has a positive and significant effect on purchasing decisions, and promotion also has a positive and significant effect on purchasing decisions. This means that these three variables have an important role in determining customer purchasing decisions